Optimization of Laser Marking Parameters on SKD-11 Tool Steel to Enhance Surface Hygiene and Safety in Medical Device Manufacturing - Karyadi; Nanda, Rizki; Mulyadi, Dodi; Suhara, Ade; Dewadi, Fathan (Public Health and Safety International Journal, 2025)
Laser marking is essential in medical device manufacturing to ensure permanent identification and traceability while maintaining hygienic surface quality. However, improper parameter selection may increase surface roughness, reducing readability and risking microbial retention. This study aims to optimize laser marking parameters on SKD-11 tool steel to improve marking clarity without compromising surface integrity. Six combinations of laser speed, power, and frequency were tested. Surface roughness was measured using a YRT200 (Ra) tester, and marking quality was visually assessed. The optimal performance was achieved at 150 mm/s, 100 W, and 54 kHz, producing clear engraving with a moderate roughness of 29.8 μm. These results indicate that appropriate parameter optimization can balance clarity and hygienic surface characteristics, highlighting its importance for reliable and safe labeling in industrial and medical applications.